The Privilege of Choice: How Prospective College Students' Financial Concerns Influence Their Choice of Higher Education Institution and Subject of Study in England - Callender, Claire; Melis, Gabriella (The Journal of higher education (Columbus), 2022)
A hallmark of English higher education (HE) over the last twenty years has been policies seeking to increase provider competition and student choice. Central to this has been student funding policy changes, leading to rising college costs. This article asks if prospective HE students' concerns about college costs and the financial strategies they anticipate using because of them, widen or limit their choice of HE institution and subject of study. It calls on the findings from a nationally representative survey of 1,374 English college applicants and uses latent class analysis to develop a typology of students' planned financial coping mechanisms: Minimizing costs; Managing costs and maximizing returns; and No financial concerns; which prove to be socially stratified. Minimizing costs students are the most disadvantaged and adopt mechanisms which constrain their choices of where and what to study, unlike students in the other groups. Thus, government policies aimed at improving student choice potentially have the opposite effect for the most disadvantaged, perpetuating existing inequalities in access to, and the experience of, HE.